Uji efektivitas antibakteri ekstrak daun kayu hitam (Diospyros celebica Bakh.) terhadap bakteri Staphylococcus aureus dan Salmonella typhi - M. Guli, Musjaya; Priyandini, Nabila; Lambui, Orryani; Ardiputra, Muh.Akbar; Toemon , Agnes Immanuela (Jurnal Kedokteran Universitas Palangka Raya, 2024)
Diospyros celebica leaf extract can inhibit the growth of Staphylococcus aureus and Salmonella typhi bacteria. This research aims to determine the ability of D. celebica leaf extract to inhibit the growth of S. aureus and S. typhi bacteria. S. aureus and S. typhi were grown in NA media and then given leaf extract with concentrations of 10%, 20%, 30% and 40% using the well method. 2% chloramphenicol added to the bacterial growth medium was used as a control. The results showed that the leaf extract from D. celebica has a strong inhibitory power to inhibit the growth of S. aureus and S. typhi bacteria.